2013
DOI: 10.1111/1365-2656.12046
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of bird functional diversity on land‐bridge island fragments

Abstract: Summary1. The loss of species diversity due to habitat fragmentation has been extensively studied. In contrast, the impacts of habitat fragmentation on functional diversity remains relatively poorly understood. We conducted bird functional diversity studies on a set of 41 recently isolated land-bridge islands in the Thousand Island Lake, China. 2. We analysed differences in bird species richness and a recently developed suite of complementary functional diversity indices (FRic, volume of functional space occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(104 citation statements)
references
References 64 publications
10
90
0
3
Order By: Relevance
“…A suite of studies, focusing on both plant and animal communities, have shown that island area plays the dominant role in controlling community recovery on TIL's islands. On the species and gene levels, plant, bird, snake, and small mammal communities have clear relationships with island area, but not island isolation (Wang et al 2010(Wang et al , 2011(Wang et al , 2012bHu et al 2011;Zhang et al 2012;Ding et al 2013;Si et al 2014Si et al , 2015aSu et al 2014;Yuan et al 2015). There are some notable exceptions to the trend of area effects dominating isolation effects (e.g., Wang et al 2012a;Yu et al 2012;Peng et al 2014).…”
Section: The Role Of Fragmentation Experimentsmentioning
confidence: 99%
“…A suite of studies, focusing on both plant and animal communities, have shown that island area plays the dominant role in controlling community recovery on TIL's islands. On the species and gene levels, plant, bird, snake, and small mammal communities have clear relationships with island area, but not island isolation (Wang et al 2010(Wang et al , 2011(Wang et al , 2012bHu et al 2011;Zhang et al 2012;Ding et al 2013;Si et al 2014Si et al , 2015aSu et al 2014;Yuan et al 2015). There are some notable exceptions to the trend of area effects dominating isolation effects (e.g., Wang et al 2012a;Yu et al 2012;Peng et al 2014).…”
Section: The Role Of Fragmentation Experimentsmentioning
confidence: 99%
“…Birds have high mobility at moderate spatial scales [62], so that the small spatial scale of our study enabled to isolate the effect of forest structure from the effects of spatial barriers to bird dispersal to sites under restoration. Forest structure can have strong effects on their avian assemblage composition [17,35].…”
Section: Discussionmentioning
confidence: 99%
“…Functional evenness, functional divergence, and functional richness (45) were calculated using the R package FD (46), based on the functional trait values for all birds on each island (the position of each species on axis 1 and axis 2 of the PCA summary of bill morphology, tarsus length, and body size). These traits were chosen because they are commonly used indicators of resource use and energy constraints (body size) (47,48), and foraging behavior in birds (bill morphology and tarsus length) (41,42). SR for each island was calculated using the land birds on each island.…”
Section: Methodsmentioning
confidence: 99%